1989
DOI: 10.1152/ajpheart.1989.257.1.h89
|View full text |Cite
|
Sign up to set email alerts
|

Transcapillary adenosine transport and interstitial adenosine concentration in guinea pig hearts

Abstract: We used the multiple-indicator-dilution technique to observe the capillary transport of adenosine in isolated Krebs-Henseleit-perfused guinea pig hearts. Tracer concentrations of radiolabeled albumin, sucrose, and adenosine were injected into the coronary inflow; outflow samples were collected for 10-25 s and analyzed by high-performance liquid chromatography (HPLC) and by gamma- and beta-counting. The albumin data define the intravascular transport characteristics; the sucrose data define permeation through i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…Similar model analyses conducted in a previous study on the same experimental model 20 revealed interstitial adenosine concentrations of 6.8 nmol/L under control conditions (our estimate, 34 nmol/L) and 191 nmol/L during membrane transport block by dipyridamole (our estimate, 94 nmol/L). Specific differences from the present study were as follows.…”
Section: Transmembranous Adenosine Concentration Gradientsupporting
confidence: 86%
“…Similar model analyses conducted in a previous study on the same experimental model 20 revealed interstitial adenosine concentrations of 6.8 nmol/L under control conditions (our estimate, 34 nmol/L) and 191 nmol/L during membrane transport block by dipyridamole (our estimate, 94 nmol/L). Specific differences from the present study were as follows.…”
Section: Transmembranous Adenosine Concentration Gradientsupporting
confidence: 86%
“…The total number of trial parameter vectors calculated to obtain the fit was 11. The values of the parameter estimates are similar to those obtained by Wangler et al (18) in similar experiments.…”
Section: Fitting the Blood-tissue Exchange Model To Multiple Tracer Osupporting
confidence: 88%
“…Near the solution for small residuals, the right hand side of Eq. 18 below is an approximation to the covariance matrix, (18) Based on the approximation, the 95% confidence interval for the parameter θ j , will be (19) where t m-p,0.95 is the Student's t-distribution with m -p degrees of freedom (17).…”
Section: Confidence Intervals Of Estimated Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods for estimating the whole heart average myocardial interstitial adenosine from measures of flows, from membrane and capillary wall permeabilities, from volumes of distribution, and from the venous outflow adenosine concentrations (Bassingthwaighte et al, 1985;Wangler et al, 1989;Gorman et al, 1991) are also indirect, but do attempt to take into account the known and measurable flow heterogeneities.…”
mentioning
confidence: 99%